Study on the Air Inlet Velocity and Temperature Distribution in an Inclined Tunnel with Single Shaft under Natural Ventilation - Liang Yi; Shihan Lan; Xiaofei Wang; Rongwei Bu; Jiaming Zhao; Yang Zhou (Buildings, 2023)
The emergence of inclined tunnels under natural ventilation has brought many new fire safety issues. The smoke movement in the tunnel is affected by the chimney effect induced by the shaft and the downstream tunnel. The characteristics of temperature distribution in inclined tunnels are different from horizontal tunnels, which is worthy of further study. A series of conditions were carried out in an inclined model tunnel with a single shaft to investigate the temperature distribution characteristics. In this study, the longitudinal air inlet velocity is used to replace the longitudinal ventilation wind velocity. Results showed that the variation of fire source location Lf,, shaft height Ls, and the tunnel slope φ have obvious effect on the air inlet velocity. Based on the previous theories and the non-dimension analysis, the formulas of the dimensionless longitudinal inlet air velocity and the distribution of the maximum smoke temperature under the ceiling are proposed, which show good consistency with the simulation results. The reduced-scale experiments were conducted to validate the results of numerical simulation. The error range between the theoretical results and the simulation results is less than 20%.